The labor market effect of demographic change: Alleviation for financing social security - Max Friese (Universität Rostock, Institut für Volkswirtschaftslehre, 2015)
The paper shows the effect of demographic change on per capita burden of financing a PAYG social security system in the standard OLG model with frictional labor markets. Rising longevity and decreasing fertility both induce a rise in the employment level via increased capital accumulation and job openings. Simulations of the theoretical model show that this labor market effect indirectly crowds out part of the initial demographic shock's direct impact on per capita financing burden. This holds true for the generation at the period of impact as well as for the following generations.
Keywords: E24; E62; H55; 330; OLG; demographic change; frictional labor market; PAYG social security; tax burden